Bataviaasch Genootschap Van Wetenschappen and the Institutionalization of Science in the Dutch East Indies 1778-1942 - Santosa, Ayi Budi; Abdurakhman, Abdurakhman; Kurniawati, Yeni; Fauzi, Wildan Insan (Diakronika, 2024)
The background of this research is that Science in Indonesia develops through institutions, not ideas, people, or instruments. This research aims to describe the institutionalization of scientific institutions in the Dutch East Indies. The historical method analyzes various resources to aid the reconstruction of the Dutch East Indies’s science institutionalization process. This research uses archives from ANRI (National Archives of the Republic of Indonesia) regarding Bataviaasch Genootschap van Wetenschappen (The Batavia Society of Arts and Science). Archives from other scientific institutions, such as Bogor and Cibodas Botanical Gardens, are also used to illustrate the institutionalization process. The findings of this research include studies on the process and the necessity to pay attention to elements such as rules, norms, cultural benefits, roles, and material resources. Institutionalizing science and technology in the Dutch East Indies underwent at least three stages: the emergence of amateur scientists from Europe, the efforts to build scientific groups, and the establishment of science institutions. This research concludes that the first two stages were outside the bureaucratic channels of the colonial government. However, in the third stage, scientists needed help to escape the role of the colonial bureaucracy in developing these scientific institutions. Bataviaasch Genootschap van Wetenschappen, founded in 1778, was a private organization studying commerce, agriculture, and humanities. It played a significant role in encouraging various other research institutions